Effect of 6-week sprint training on long-distance running performance in highly trained runners - Ando, R.; Kojima, C.; Okamoto, S.; Kasai, N.; Sumi, D.; Takao, K.; Goto, K.; Suzuki, Y. (International Journal of Sports Physiology and Performance, 2024)
Purpose Long-distance running performance has been reported to be associated with sprint performance in highly trained distance runners. Therefore, we hypothesized that sprint training could enhance distance running and sprint performance in long-distance runners. This study examined the effect of 6-week sprint training on long-distance running and sprint performance in highly trained distance runners.